Transformation of PPCPs in the environment: Review of knowledge and classification of pathways according to parent molecule structures. Issue 1 (2nd January 2023) - Bonnot, Kevin; Benoit, Pierre; Mamy, Laure; Patureau, Dominique
Abstract: Reviewing the transformation pathways and analyzing the reactions undergone according to the matrices and the parent compound chemical structures may help to progress in our understanding of transformation processes of PPCPs. Of the 199 parent molecules initially targeted, 42% had no information on their transformation products (TPs). The transformation of the remaining 116 PPCPs led to 1371 TPs formed by biotic (630), abiotic (568), and both biotic and abiotic (61) reactions in natural (solid waste, natural waters, soils, WWTP effluents, sediments) and/or synthetic matrices. For a small number of TPs (112) no information was found on the conditions of their formation. Eleven main transformation reactions (hydroxylation, dehydrogenation, cleavage, hydrolysis, dealkylation, oxygenation, dehalogenation, other eliminations, other substitutions, addition and rearrangement) were considered to describe the TPs dataset, that ended up with 3230 individual reactions (one TP can result from several successive reactions). Hydroxylation was the major reaction occurring at 28% followed by dehydrogenation (13%), then cleavage (11%). A majority of studies were performed in synthetic media whereas knowledge on transformation reactions in environmental matrices is very heterogeneous with less information on soils and sediments. Finally, we aimed at assessing the relationship between the transformation reactions and the chemical structures of the parent molecules using 1178 molecular fragments and molecular descriptors. Several clusters composed of sulfonamides, cyclines or macrolides showed trends between functional groups and reactions involved in the transformation pathways. Based on these data and results, some research needs were highlighted.